2013
DOI: 10.1080/09064702.2013.793734
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of grass/clover silage in the diet of growing/finishing pigs – Influence on pig time budgets and social behaviour

Abstract: This study investigated how inclusion of grass/clover silage affected the time budgets and social behaviour of growing/ finishing pigs. The behaviour of 128 pigs was observed through video recordings. Pigs fed intact or chopped silage spent a larger proportion of their time active compared with pigs fed silage in pelleted form or fed only cereal-based feed. There was a trend for pigs fed silage in pelleted form or fed only cereal-based feed to respond strongly to social interactions more often than pigs fed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 14 publications
3
14
0
Order By: Relevance
“…In the present study, pigs with access to silage were more active and spent less time lying down than pigs in the control treatment without silage. As shown previously by Høøk Presto et al (2009) and Presto et al (2013), access to silage stimulated the pigs to be more active than when only straw was provided as an enrichment (control treatment). The pigs provided with chicory and red clover silage spent a higher proportion of their time in the pen lying area and up to twice as much time nosing/rooting on the pen floor than the pigs in the control treatment.…”
Section: Time Budgetssupporting
confidence: 59%
See 2 more Smart Citations
“…In the present study, pigs with access to silage were more active and spent less time lying down than pigs in the control treatment without silage. As shown previously by Høøk Presto et al (2009) and Presto et al (2013), access to silage stimulated the pigs to be more active than when only straw was provided as an enrichment (control treatment). The pigs provided with chicory and red clover silage spent a higher proportion of their time in the pen lying area and up to twice as much time nosing/rooting on the pen floor than the pigs in the control treatment.…”
Section: Time Budgetssupporting
confidence: 59%
“…There were fewer behaviours directed at other pigs and pen fittings among the pigs provided with silage. Pigs deprived of opportunities to forage and explore their surroundings may redirect those behaviours towards other pigs in the pen and pen fittings (Lyons et al 1995;Beattie et al 2000;Presto et al 2013). In agreement with this, performing behaviour such as nosing at other pigs also occurred less frequently among pigs in the chicory and red clover treatments than pigs in the control.…”
Section: Social Interactionsmentioning
confidence: 60%
See 1 more Smart Citation
“…Large differences in behaviour between pigs reared in barren respectively enriched environments have been found (Petersen et al, 1995;Beattie et al, 1996Beattie et al, , 2000. Presto et al (2013) showed that pigs fed TMR with chopped silage or intact silage in a rack, spent a larger proportion of their time foraging compared with pigs fed only pelleted feed and straw as enrichment. The present study confirmed that TMR with inclusion of silage that was intensively manipulated for a shorter particle length and finer structure (SI) increased the silage consumption to be almost fully completed.…”
Section: Discussionmentioning
confidence: 99%
“…Pigs' consumption of silage, however, varies according to their age (Wüstholz et al, 2017), the type of ley crops included, nutrient content as well as feeding technique and structure of the silage (Rundgren, 1988;Høøk Presto et al, 2009;Presto Åkerfeldt et al, 2019). The latter has also been found to influence the pigs' behaviour (Presto et al, 2013;Wallenbeck et al, 2014). It was found that when grass/clover silage replaced 20% of the energy in diets to pigs, either fed (intact in a rack) or in a total mixed ration (TMR) (silage was chopped and mixed with the other feed ingredients), the pigs sorted out parts of the silage.…”
Section: Introductionmentioning
confidence: 99%